Mahar dan nafkah sebagai hak pemilikan harta wanita dalam konteks kesaksamaan gender - Awang, Abdul Bari; Awang Abd. Rahman @ Jusoh, Amilah (IKIM Press, 2015)
Of late, gender equity, in the sense of justice applicable to both men and women, has become a hotly debated issue. As one of the world’s major religions, Islam’s position on the issue has also been subject of scrutiny and unfortunately, on several occasions, has been viewed with suspicions and seen as unbalanced. Islam is often regarded as a religion that prioritises men over women; men seem to possess more rights not only in such cases as polygamy and marital divorce but also in the possession of wealth through inheritance. This article attempts to provide a balanced view on the aforementioned issue by exploring the rights of women as stipulated in Islam, especially the rights of wealth possession (ḥuqūq māliyyah) in the family as an institution. In general, the article examines whether or not the existing rights of women render them on a par with men in regard to wealth possession. Specifically, this article addresses issues of dowry (mahr) and maintenance (nafaqah), as well as their impacts in elevating women’s position. Being an analysis based on primary sources of Islam, namely, the Qurʾān, the sunnah of the Prophet, as well as classical scholars’ discussions, the article concludes that, as far as Islam is concerned, gender equity is indeed realisable on the conditions that womens’ rights in Islam are well understood and sincerely fulfilled by all parties involved.